Gender, Information and the Efficiency of Household Production Decisions: An Experiment in Rural Togo - Marie Christine Apedo-Amah; Habiba Djebbari; Roberta Ziparo (Institute of Labor Economics (IZA), 2020)
Why do farm households inefficiently allocate resources across the plots they cultivate? We explore how these production inefficiencies relate to consumption decisions and information sharing within the household. In a lab-in-the-field experiment, male producers allocate too few inputs to their wife's plot, failing to maximize household aggregate profits. They do transfer more inputs when the returns from that plot are higher. Experimental manipulation of information on these returns triggers heterogenous responses across households. We provide a theoretical framework that rationalizes these findings and further leads to sharp predictions. Joint contribution to a household public good compels spouses to make efficient production decisions. Only households who are in a separate-sphere regime experience inefficiency in farm production and are unable to effectively communicate on returns to avoid extra losses. Consistent with this framework, when we experimentally offer an ex post information verification mechanism, additional losses due to information asymmetries are prevented.
Keywords: Q12; C72; D13; D82; C91; C93; 330; farm households; household production and intra-household allocation; non-cooperative game theory; asymmetric and private information; lab-in-the-field experiment